Attention Dynamics in Spatial–Temporal Contexts - Yuying Wang; Xuemin Zhang; Eva Van den Bussche (Behavioral Sciences)
This study systematically explored the impact of the spatial metaphor of time on attentional bias using visual order stimuli. Three experiments were conducted. Experiment 1, comprising Experiments 1a and 1b, investigated how the spatial metaphor of time shaped attentional bias across five disorder levels. Experiment 1a examined horizontal orientations, while Experiment 1b focused on vertical orientations. Experiment 2 compared attentional biases toward stimuli with the same disorder level in both orientations. The key distinction between the stimuli was that one represented short-term memory, while the other did not involve memory. Building on the findings of Experiment 2, Experiment 3 compared attentional biases between fully ordered structures (intact Gestalt structures) as non-memory representations and partially disordered structures in short-term memory. The results revealed a significant preference for future-related information, particularly on the right side in horizontal orientations. Short-term memory representations enhanced attentional attraction and triggered inhibition of return (IOR), while fully ordered structures attracted attention as effectively as partially disordered structures, thereby neutralizing attentional biases. Overall, this study contributes to a deeper understanding of the cognitive mechanisms underlying visual attention and the influence of temporal metaphors.